Application and Cutting Machining of Double Disc Milling Cutter - Li Zhijiang (Jixie chuandong, 2016)
The CNC milling machine has the advantages of simple movement and high efficiency in manufacturing large modulus cylindrical gear. In order to improve the processing efficiency of rough milling,a method based on the double disk milling cutter is proposed for large modulus cylindrical gear. For one thing,the change law between the tooth profile allowance and the gear modulus with double,single disc milling type is obtained by establishing the mathematic model of tooth groove allowance of double disk milling. For another thing,in contrast with the traditional single disk milling,the time cost model,cutting- tool wear cost model and follow- up hobbing cutting wear cost model are established to investigate the relationship between the cutting cost and workpiece modulus for double disk milling. Finally,the feasibility of double disk milling is verified by an example of machining large modulus as well as the torque and force experiment. The experimental results show that the double disk milling method is a good solution for rough milling of large modulus gear.